The Influence of the Distribution Process and Customer Satisfaction on Customer Loyalty (Case Study of the Cakung Distribution Center on Courier Company) - Nofrisel Nofrisel Nofrisel; Sekar Widyastuti Pratiwi; Astry Salsyabila Zaira; Nita Ayu Putriani (Dinasti Review, 2025)
This study aims to analyze the effect of the distribution process and customer satisfaction on customer loyalty on express companies. With a deeper understanding of customer loyalty theory, this study seeks to measure customer loyalty levels and determine their position on the loyalty scale. The approach used in this study is a quantitative approach, which will provide statistically quantifiable data. With the help of the PLS analysis tool, this study is expected to have valid results on the effect of independent variables, namely distribution process (X1) and customer satisfaction (X2), on dependent variables, namely customer loyalty (Y). The results of this study are expected to provide practical recommendations and for company management to improve distribution quality and customer satisfaction.